Supporting Ghana's agricultural mechanization program to better meet the needs of smallholder farmers - CGIAR Research Program on Policies, Institutions, and Markets; Takeshima, Hiroyuki (International Food Policy Research Institute, 2020)
With support from PIM and USAID, researchers from IFPRI and CIMMYT together with Ghana government officials conducted a qualitative assessment of the Ghana Agricultural Mechanization Service Enterprise Centers (AMSECs) program. The recommendations from the study were used to improve the program’s inclusiveness and efficiency.